2010
DOI: 10.1080/13825580903311832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on the Temporal Organization of Working Memory in Deaf Signers

Abstract: Temporal organization in WM 2Deaf native signers have a general working memory (WM) capacity similar to that of hearing non-signers but are less sensitive to the temporal order of stored items on retrieval. General WM capacity declines with age, but little is known of how cognitive aging affects WM function in deaf signers. We investigated WM function in elderly deaf signers (EDS) and an age-matched comparison group of hearing non-signers (EHN) using a paradigm designed to highlight differences in temporal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
(120 reference statements)
0
14
0
Order By: Relevance
“…According to this view, whereas speakers strongly rely on the phonological loop for the storage and recall of linguistic information in WM tasks, signers instead rely on integrated multidimensional memory representations in the episodic buffer that include phonological information, but also, for instance, semantic and spatial information (e.g. Hirshorn et al, 2012; Rudner et al, 2009, 2010, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this view, whereas speakers strongly rely on the phonological loop for the storage and recall of linguistic information in WM tasks, signers instead rely on integrated multidimensional memory representations in the episodic buffer that include phonological information, but also, for instance, semantic and spatial information (e.g. Hirshorn et al, 2012; Rudner et al, 2009, 2010, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Bavelier, Newport, Hall, Supalla, & Boutla, 2006, 2008; Boutla, Supalla, Newport, & Bavelier, 2004; Geraci, Gozzi, Papagno, & Cecchetto, 2008; Hall & Bavelier, 2011; Wilson, Bettger, Niculae, & Klima, 1997; but see also Andin et al, 2013; Wilson & Emmorey, 2006a, 2006b). Importantly, modality differences are typically not found in backwards serial recall tasks or in tasks with reduced temporal organization demands, such as free recall (e.g., Bavelier, Newport et al, 2008; Boutla et al, 2004; Rudner, Davidsson, & Rönnberg, 2010; Rudner & Rönnberg, 2008a). Moreover, some studies have found that signers outperformed speakers on spatial serial recall tasks, such as the Corsi block test (e.g., Geraci et al, 2008; Romero et al, 2014; Wilson et al, 1997; but see Logan, Mayberry & Fletcher, 1996; Marschark et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, other work has shown that effects of phonological similarity on WM for sign language can be elusive (Rudner & Rönnberg, 2008a) despite effects of semantic category 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 (Rudner et al, 2010;Rudner & Rönnberg, 2008a). Indeed in a recent study, it was shown that although deaf users of SSL displayed an effect of phonological similarity on the short term store, as measured by digit span, this effect did not generalize to digit-based WM, as measured by operation span, and when the same experiment was performed with deaf users of BSL, no clear effect of phonological similarity was discernible for either the shortterm store or WM (Andin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Group size was estimated on the basis of previous experience with mixed repeated-measures designs, e.g. Rudner, Davidsson and Rönnberg (2010). Details of the groups are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…67 Executive functioning consists of multiple components—ie, working memory, controlled attention, self-monitoring, organisation, inhibition, flexibility-shifting, and goal direction. 68 Verbal working memory, 69,70 controlled cognitive fluency, 67,71 re distribution of attentional resources, 21,72,73 and inhibition–concentration are at risk for delays in individuals with early deafness despite cochlear implantation. 66,74,75 Verbal working memory is assessed with neurocognitive methods that require individuals to hold a sequence of familiar verbal stimuli— eg, digits, letters, or words—in immediate memory while simultaneously engaging in another cognitive activity, such as reversing the order of test items or completing a simple mental calculation (appendix).…”
Section: Clinical Assessment Of Neurocognitive Outcomesmentioning
confidence: 99%